POTRET SOLIDARITAS YESUS BAGI KAUM MISKIN DAN RELEVANSINYA BAGI ROHANIAWAN - Simon Simon; Auw Tammy Yulianto; Daniel Ronda (Manna Rafflesia, 2023)
This article laid out specifically the portrait of Jesus' solidarity with the poor or marginalized groups who were often socially left out, neglected and even discriminated. This topic was elaborated on, given that human empathy was slowly fading. In portraying Jesus' solidarity, the researchers traced it from the Gospel of Luke because this book paid severe attention to Jesus' solidarity with the poor. The researchers used the exposition and literature approach to outline the topic of this article. The findings of this study suggested that the portrait of Jesus' solidarity for the poor and marginalized people was that He embraced the left out, met their physical and spiritual needs, defended those who were discriminated and helped thoroughly. The act of solidarity shown by Jesus depicted that He shared their burden, felt how they felt, and sensed the suffering of the poor and other marginalized groups. The solidarity that Jesus became the role model for every servant of God, to follow and emulate what He did as God's partner in echoing the kingdom of God.